Affordable but Adequate? Effectiveness of Rusunawa for Low-Income Housing in Cepu - Hapsari, Primerta Putri; Ishaq, Agung Bahagia; Ismiyati, Nur (Indonesian Journal of Agrarian Law, 2024)
The effectiveness of simple rental apartments (rusunawa) as a housing solution for low-income communities (MBR) is examined using the case study of the Cepu Rusunawa in Blora Regency. The housing backlog in Indonesia, which will reach 12.7 million units by 2023, with 84% of the population remaining homeless, is the background to the urgency of this research. The rapid rate of urbanization of 3% per year, with a projection that 66.6% of Indonesia's population will live in urban areas by 2035, further emphasizes the importance of vertical housing solutions. The research method employed a normative legal study approach. Data analysis was conducted through qualitative methods, utilizing legal, conceptual, and comparative perspectives for policy analysis related to the implementation of Law No. 20 of 2011 concerning Flats. The results indicate that the Cepu Rusunawa, built with an investment of IDR 15.8 billion from the state budget and inaugurated in February 2017 with 98 residential units, faces significant challenges in its management. Despite initial interest, occupancy has declined, with 30 of the 99 units vacant by 2023. Several inhibiting factors exist, including unclear management status between the central and regional governments, and the need for a comprehensive evaluation of service quality and the physical condition of the buildings. A holistic and collaborative approach from all stakeholders is needed to optimize the function of the low-cost apartments as a sustainable, affordable housing solution.